The association of urinary BDNF, ATP, and MMP-2 with bladder compliance in children with myelodysplasia - ŞEKERCİ, ÇAĞRI AKIN; KÜTÜKOĞLU, MEHMET UMUT; YÜCEL, SELÇUK; TARCAN, TUFAN (My University, 2023)
Aim: The purpose of our study was to evaluate the relationship of urinary brain-derived neurotrophic factor (BDNF), adenosine triphosphate (ATP), matrix metallopreteinase-2 (MMP-2) with urodynamic findings and upper urinary tract deterioration (UUTD) in children with myelodysplasia. Materials and Methods: Children with myelodysplasia evaluated in outpatient clinic between 2022 and 2023 were included. All patients underwent urinary ultrasonography, voiding cystourethrography, urodynamics, and DMSA scintigraphy. Urine samples were collected before urodynamics. Control urine was collected from 10 healthy children. Urinary biomarker values of patients and controls were compared, and subgroup analysis was performed. Results: The median age of 40 children (26 girls) included in the study was 108 (8–216) months, and the control group (six girls) was 120 (60–154) (p = 0.981). Urinary BDNF, MMP-2, and ATP were found to be significantly higher in children with myelodysplasia compared to the control (p = 0.007, p = 0.027, p = 0.014, respectively). The three biomarker values were similar in children with bladder compliance below or above 10 cmH2O/mL (p = 0.750, p = 0.844, p = 0.575). No difference was found in terms of UUTD in all three biomarkers (p = 0.387, p = 0.892, p = 0.705). A negative correlation was found between urinary ATP and compliance (p < 0.05). Conclusion: In this study, all three biomarkers were found to be higher in children with myelodysplasia than in controls. There was a negative correlation between urinary ATP and compliance. Urinary biomarkers may contribute the follow-up of children with neurogenic lower urinary tract deterioration in future with their noninvasive features. However, the lack of standardization and the inability to reliably predict risky groups are important shortcomings of urinary biomarkers.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Nöroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Neurology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; KLİNİK NÖROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; CLINICAL NEUROLOGY; Nöroloji (klinik); Üroloji; Neurology (clinical); Urology; ATP; BDNF; children; MMP-2; myelodisplasia; urodynamics